CupCake Y’Alls / Hasbi Megat Zafirus ... [et al.] - Megat Zafirus, Hasbi; Rosli, Muhammad Hakimi; Rahim, Nur Athirah; Azhar, Nur Nabilah; Nor Hisham, Siti Hajar; Mohd Ghani, Siti Zulaikha (2021)
CupCake Y’Alls is a local business that offers various types of ingredients and flavors to gives a higher satisfaction level to the customer. We specifically made a dessert that innovatively customizing a cupcake that has a different taste at an affordable price. Our business embodies 6 people which is Hasbi Megat, Nur Athirah, Nur Nabilah, Siti Hajar, Hakimi Rosli, and Siti Zulaikha. The idea of this business is purposely to reach out to the standard of Malaysian taste desired that is comprised of different categories of customers. We commenced this business in 2021 on may that located in Petaling Jaya, Selangor. Hence, this report will include meticulous information on our Business Model Canvas. The report begins with our company background that portrays further information of Name of the company, vision, and mission which mainly produced the best product with an outstanding standard. To be added, this company operated with a partnership of seven members which the profits and loss are divided together. The product that is offered by our business simply is a dessert with a variety of flavors in cupcakes to expand customer categories. We also made a problem statement which to ensure our decision is accurate since it is a unique product compared to others. With this, the problem that is faced by the business will be solved by using three implementations that be made up of price, marketing, and operations strategies. On other hand, we also putting Opportunity Recognition which a process to view our company possibilities to be a more successful business. Furthermore, we also applied SWOT Analysis to see our business strengths and flaws. In addition, for our analysis, we compared the SWOT from two of our competitors which are from HOMEMADES SWEET and KEDAI KEK WARISAN. These details from our competitors are significant for our own company SWOT Analysis as to be efficient in running a business. The next part of this report will provide the vital company information of Business Proposal which particularly about our Business Model Canvas and their explanation. Moreover, the explanation of the BMC will be divided into different elements of customer segments, Value propositions, Channels, Customer Relationships, Revenue Streams, Key Activities, Key Resources, Key Partnership, and Cost Structure. This model can be considered as the strategic method where we can effortlessly view and carry out our business concept or idea. In a nutshell, the Business Model Canvas Report writes down the data and important elements for CupCake Y’Alls to reach out desire outcome.